2020
DOI: 10.1101/2020.07.12.20151084
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prehospitalization Proton Pump Inhibitor (PPI) use and Clinical Outcomes in COVID-19

Abstract: Introduction There is a concern that proton pump inhibitors (PPI) induced hypochlorhydria could potentially predispose to severe COVID-19. Methods We studied the association between prehospitalization PPI use and clinical outcomes among hospitalized COVID-19 patients. Results In our study, 15.6% of hospitalized COVID-19 patients were on PPI. Mortality among PPI-users was 2.3 times higher than non-users, along with 2.5 times higher risk of mechanical ventilation. This relationship existed even after adjusting … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…These results were consistent with our leaveone-out sensitivity analysis (online supplemental figure 4), indicating that this association was strong. Furthermore, current PPI users tended to hospitalised longer than PPI non-users, although not by a statistically significant margin (n=353 from two studies; 7 14 MD 1.13, 95% CI −0.18 to 2.43, p=0.09; figure 2). Finally, past use of PPIs was not associated with increased susceptibility to SARS-CoV-2 infection (n=1 72 833 from four studies; 1 3 5 6 OR 0.85, 95% CI 0.57 to 1.27, p=0.43; I 2 =92%; figure 1) or with severe outcomes of COVID-19 (n=40 097 from three studies; 1 3 9 OR 1.03, 95% CI 0.85 to 1.23, p=0.79; I 2 =0%; figure 2).…”
Section: Do Proton Pump Inhibitors Influence Sars-cov-2 Related Outcomentioning
confidence: 99%
“…These results were consistent with our leaveone-out sensitivity analysis (online supplemental figure 4), indicating that this association was strong. Furthermore, current PPI users tended to hospitalised longer than PPI non-users, although not by a statistically significant margin (n=353 from two studies; 7 14 MD 1.13, 95% CI −0.18 to 2.43, p=0.09; figure 2). Finally, past use of PPIs was not associated with increased susceptibility to SARS-CoV-2 infection (n=1 72 833 from four studies; 1 3 5 6 OR 0.85, 95% CI 0.57 to 1.27, p=0.43; I 2 =92%; figure 1) or with severe outcomes of COVID-19 (n=40 097 from three studies; 1 3 9 OR 1.03, 95% CI 0.85 to 1.23, p=0.79; I 2 =0%; figure 2).…”
Section: Do Proton Pump Inhibitors Influence Sars-cov-2 Related Outcomentioning
confidence: 99%
“…Table 1 outlines the risk factors for COVID-19 infection and poor outcomes [ 2 - 4 , 7 , 13 , 51 ]. Recent evidence suggests that the use of proton pump inhibitors is associated with an increased risk of SARS-CoV-2 infection and also potentially increases the risk of poor outcomes, such as death and mechanical ventilation [ 52 , 53 ].…”
Section: Risk Factors For Sars-cov-2 Infection In Ibdmentioning
confidence: 99%
“…The pooled analysis of studies by McKeigue et al [5], Ramachandran et al [6] and Lee et al [4] revealed a significantly increased odds for a severe or fatal course of COVID-19 with the use of PPIs in COVID-19 patients relative to nonuse of PPIs ( Fig. 1; pooled OR = 1.46; 95% CI 1.34-1.60).…”
mentioning
confidence: 96%
“…Five studies that corresponded to inclusion criteria with a total of 37 372 patients were included for our meta-analysis [1,[4][5][6]. Study characteristics are depicted in Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation